Work Engagement as a Mediator of the Influence of Coworker Support on Task Performance of Indonesian Army (TNI-AD) Soldiers Serving in Vulnerable Areas (Papua) - Tian Sakti Marantika; Endang Parahyanti (Budapest International Research and Critics University, 2021)
Army is one of particular profession which has extremely high-risk job. Most of Indonesian Army member will be deployed to a danger area that has dynamics situation. Coworker support is needed for them to increase soldier work engagement and enabling them to show their best performance in a deployment. Data collection methods used in this research was survey method by using Coworker Support Scale Items (2002), Individual Work Performance Questionnaire (2012), and Utrecht Work Engagement Scale/ UWES (2002). The participants of the study were 541 Indonesian Army whom deployed in danger area. Data processing and analysis were using Hayes PROCESS Procedure model 4 program (Simple Mediation). The result shows that the presence of high Coworker’s support would increase for work engagement and eventually enabling soldiers to perform their best on the deployment.